2012
DOI: 10.5897/jmpr11.1349
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and antioxidant activities of Mimosaceae plants; Acacia modesta Wall (Phulai), Prosopis cineraria (Linn.) and Prosopis juliflora (Swartz)

Abstract: Antimicrobial and antioxidant activities of Mimosaceae plants; Acacia modesta Wall (Phulai), Prosopis cineraria (Linn.) and Prosopis juliflora (Swartz) In the present study the methanolic leaf extracts of three plant species of family Mimosaceae viz., Acacia modesta Wall (Phulai), Prosopis cineraria (Linn.) Druce and Prosopis juliflora (Swartz) DC. were used to evaluate their antibacterial antifungal and antioxidant activity. Simple maceration method was used for the preparation of plant extracts. The extracts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…The ethanolic extract of T. aphyla showed remarkable activity against sixteen Gram-positive and Gram -negative bacterial strains. As compared to the standard drug, the highly significant activity of Acacia modesta and other medicinal plants extracts was recorded by Napar et al 15 against S. aureus, B. subtilis and E. coli. The stem extracts of A. modesta with five bacterial strains showed that this specific part of the plant has profound antibacterial activity, and same results were noted by 17 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ethanolic extract of T. aphyla showed remarkable activity against sixteen Gram-positive and Gram -negative bacterial strains. As compared to the standard drug, the highly significant activity of Acacia modesta and other medicinal plants extracts was recorded by Napar et al 15 against S. aureus, B. subtilis and E. coli. The stem extracts of A. modesta with five bacterial strains showed that this specific part of the plant has profound antibacterial activity, and same results were noted by 17 .…”
Section: Discussionmentioning
confidence: 99%
“…The dried bark of this tree is conventionally used in Pakistan for improving oral hygiene and promoting teeth brightening. Earlier studies reported the antimicrobial activity of this plant against bacteria and fungi that may be due to the presence of polyphenols 1,2,[9][10][11][12][13][14][15] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…En la corteza de Prosopis Juliflora se encontró una correlación entre la concentración de un extracto y la inhibición de radicales libres de DPPH (Siahpoosh y Mehrpeyma, 2014). Otros extractos de especies de Prosopis han mostrado capacidad antioxidante, como los extractos metanólicos de hojas de P. cineraria y P. juliflora (Napar et al, 2012). Poudineh et al (2015) evaluaron el efecto de los solventes etanol, metanol, octanol y n-heptano sobre las actividades antioxidantes y antibacterianas de los extractos de semillas y vainas de P. farcta, el mayor contenido fenólico y la mayor actividad se obtuvo al utilizar octanol como solvente de extracción.…”
Section: Capacidad Antioxidanteunclassified
“…Gum acacia is a complex polysaccharide exudate, that is obtained from the trees of Acacia species, this exudate protects the tree against the external attacks 14 . Antimicrobial potential of extracts of leaves and stem has also been estimated that leads to use of young twigs of this plant as tooth stick (miswak) 15,16 . Hepatoprotective potential of A. modesta (Bark extract) has also been reported in plasma proteins level and serum levels of hepatic metabolic enzymes were used for the analysis of hepatotoxicity 17 .…”
Section: Introductionmentioning
confidence: 99%